On the Origin of Donut‐Shaped Electron Distributions Within Magnetic Cavities - Jing‐Huan Li; Xu‐Zhi Zhou; Qiu‐Gang Zong; Fan Yang; Suiyan Fu; Shutao Yao; Ji Liu; Quanqi Shi (Geophysical Research Letters)
Abstract Magnetic cavities, also known as magnetic holes, are ubiquitous in space plasmas characterized by depressed magnetic strength and enhanced plasma pressure. Most of the observed cavities are associated with anisotropic particle distributions with higher fluxes in the direction perpendicular to the magnetic field. Recent observations of kinetic‐scale magnetic cavities have identified another type of electron distributions in the pitch angle spectrum, the so‐called donut‐shaped distributions, although their formation mechanism remains unclear. Here, we present a simplistic model of cavity shrinkage and deepening, in which electrons are traced backward in time to the initial, equilibrium‐state cavity. The resulting electron distributions, determined from Liouville's theorem, agree with the observations in the presence of donut‐shaped pitch angle structures. The model also enables a quantitative evaluation on the roles of betatron cooling, radial transport, and pitch angle variations in the formation of donut‐shaped electron distributions within evolving magnetic cavities.